Sight for All United: Five Year Impact of a Vision Foundation on its Community - Ankur Parikh; Meredith Spitz; Cooper T. Johnson; S.A. Erzurum (Ohio Journal of Public Health, 2021)
Background: In 2016, Sight for All United (SFAU) was founded in the Mahoning Valley of Ohio with the mission of improving access to care and maximizing the visual potential of the underserved. Methods: A retrospective chart review was conducted on patients served by SFAU from January 2016 through August 2020. Socioeconomic information, type of service, cost, and dollar amount paid were collected for patients. The data were analyzed with descriptive statistics and mapped with Esri ArcGIS. Results: A total of 1327 patients received assistance through the medical assistance and school vision programs. In the medical assistance program, 222 patients (mean age 50 years, 57% female) completed applications and 37% (83 patients) were in a household of 3 or more people. Median yearly income was 18 504, 134% above the federal poverty level by household size. The most common surgical services were cataract surgery (101) and vitreoretinal care (17). The most common medical services were eye exams (79) and spectacles (76). Estimated value of medical services provided was 367 249; actual cost was 93 746. The school vision program provided 1105 eye exams, 1514 pairs of spectacles, and 1 cataract surgery with an estimated value of 133 692. Conclusion: Sight for All United provided 500 941 of vision services to its patients since 2016 while dispersing less than 100 000 of donated dollars through collaboration with eye care providers, community resources, and national foun-dations. This study demonstrates the impact vision foundations managed by local eye care providers can have on the needs in their community in a cost-effective and efficient way.
Keywords: Nonprofit; Vision; Ophthalmology; Mahoning Valley